Implementasi Hotspot Internet Dengan User Manager Dan Manajemen Bandwidth Di Sman 1 Kutorejo - Arif Rahman Sujatmika; ferry sumarsono sumarsono; Muhammad Gugus Azhari (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
This research is motivated by the development of information and communication technology which results in the need for internet access to increase among the community, especially in the field of education. The use of the internet in education is very supportive in the teaching and learning process, because with this media students and teachers can more easily access the internet. However, the obstacles that are often experienced are the difficulty of accessing material and knowing the latest information about education, the network devices used are still limited so they cannot reach all areas of the school, so a hotspot is needed by dividing users, bandwidth, and access rights to make it easier for teachers and students in accessing the internet network, as well as limiting student access rights so as not to use the internet incorrectly, in supporting the development of this network, additional network devices are needed, namely mikrotik and access points. The purpose of this study is to analyze how the right design is so that internet connections are more optimal for use, design a bandwidth management system, optimize internet users' logins according to what is specified.